On the interrelation between carbon offsetting and other voluntary climate protection activities: Theory and empirical evidence - Andreas Lange; Claudia Schwirplies; Andreas Ziegler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This paper provides theoretical and empirical insights on the extent to which the availability of carbon offsetting may substitute the individual use of other carbon-reducing measures. Theoretically, we demonstrate an ambiguous impact of offsetting on the use of other measures and derive conditions under which both are substitutes or complements. We then empirically test our predictions using data from representative surveys among more than 2000 citizens in Germany and the U.S. Considering seven measures that can be taken by individuals to directly reduce greenhouse gas emissions, our empirical evidence is consistent with the theoretical predictions that substitution occurs particularly if individuals lay a sufficiently large weight on environmental preference or if offsetting is perceived to be relatively effective in providing the public good climate protection. Complementary effects are shown to exist for a perceived intermediate effectiveness of offsetting activities.
Keywords: C25; Q54; Q58; 330; climate change; climate protection; green consumption; carbon offsetting; complement; substitute; impure public goods